Salvage Surgery for Patients With Local Recurrence or Persistent Disease After Treatment With Chemoradiotherapy for SCLC - Pieter J.M. Joosten, MD; Toon A. Winkelman, MD; David J. Heineman, MD, PhD; Sayed M.S. Hashemi, MD; Idris Bahce, MD, PhD; Suresh Senan, MD, PhD; Marinus A. Paul, MD, PhD; Koen J. Hartemink, MD, PhD; Max Dahele, MbChB., PhD; Chris Dickhoff, MD, PhD (JTO Clinical and Research Reports, 2021)
Introduction: The role of salvage surgery for patients with locoregional (LR) recurrence or persistent SCLC after radical chemoradiotherapy (CRT) for limited-stage disease is not well established. We evaluated our experience. Methods: We conducted a retrospective study of consecutive patients who underwent salvage pulmonary resection for LR-recurrent or persistent SCLC between 2008 and 2020 at the Amsterdam University Medical Center. Results: A total of 10 patients were identified. Median age at initial diagnosis of limited-stage SCLC was 58.5 years (48–71 y). All patients had radical-intent concurrent CRT. Of the 10 patients, 9 were diagnosed with LR-recurrent or persistent disease with a median of 18 months (3–78 y) after CRT. All patients underwent an anatomical radical resection and mediastinal lymph node dissection. No 90-day mortality was recorded. In addition, one patient developed a LR recurrence 7 months after resection. Distant progression was found in three patients at 6, 32, and 61 months after surgery, all of whom subsequently died of progressive SCLC. Median follow-up was 22.5 months (2–86 mos). Disease-free survival was 34 months; overall survival was not reached. Conclusions: For highly selected patients with LR-recurrent or persistent SCLC after CRT, salvage surgery is feasible and can result in clinically meaningful survival. Such patients should be presented to the multidisciplinary tumor board.